THE INFLUENCE OF MOTIVATION, COMPETENCE AND WORK ENVIRONMENT TOWARDS EMPLOYEE PERFORMANCE AT MANADO CITY TOURISM OFFICE - Maryam Mangantar; Rorong, Natalia; Rogi, Mira (Universitas Sam Ratulangi, 2024)
This study aims to analyze the influence of motivation, competence, and work environment on employee performance at the Manado City Tourism Office. Employee performance is an important factor in achieving organizational goals, especially in the tourism sector which requires qualified employees to provide optimal service. This study uses a quantitative method with a survey approach through questionnaires distributed to employees of the Manado City Tourism Office. The data was analyzed using multiple linear regression techniques to determine the influence of independent variables (motivation, competence, and work environment) on dependent variables (employee performance). The results of the study show that motivation, competence, and work environment have a significant influence on employee performance, both partially and simultaneously. The conclusion of this study is that increasing motivation, competence, and a conducive work environment can improve employee performance, which will ultimately have a positive impact on operational effectiveness at the Manado City Tourism Office. Keywords: Motivation, Competence, Work Environment, Employee Performance